The eﬀect of active release versus ischemic pressure techniques in pain, range of motion, function, and pressure pain threshold on females with piriformis syndrome: a randomised controlled clinical trial - Zaghlol, Aya A.; Elsayed, Wadida H.; Azzam, Ahmad H.; Grase, Mariam O. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. To compare the eﬀects of active release technique (ART) versus ischemic pressure technique (IPT) in females with piriformis syndrome and active trigger points.Methods. Forty-ﬁve females with active trigger points in the middle of the piriformis muscle. Participants were randomly allocated to three equal groups according to the chit method of randomisation. The conventional group received conventional physical therapy treatment composed of 20 min of hot packs, 20 min of TENS, and 3 min of stretching. The IPT group received conven-tional physical therapy treatment and IPT. The ART group received conventional physical therapy treatment and ART. Each group received two sessions per week for 6 weeks. Primary outcomes included pain intensity levels measured by the visual analogue scale and hip internal rotation range of motion measured by a manual goniometer. Secondary outcomes included lower extremity function disability measured by the lower extremity function scale and the pressure pain threshold measured by a manual algometer.Results. Mann–Whitney U analysis revealed a signiﬁcant diﬀerence post-treatment in favour of the IPT group compared to the conventional and IPT groups and a signiﬁcant diﬀerence in favour of the ART group compared to conventional and ART groups (p < 0.05). Both techniques proved to be superior compared to the conventional treatment; however, there was no signiﬁcant diﬀerence between IPT and ART (p > 0.05).Conclusions. The addition of ART or IPT to conventional physical therapy in females with active piriformis trigger points re-duces pain intensity, increases internal rotation of the hip, and improves lower extremity functional ability.
Keywords: piriformis muscle syndrome; ischemic pressure technique; active release technique; musculoskeletal manipulations; trigger points